Bio-based and sustainable food packaging systems: relevance, challenges, and prospects - Leticia Donkor; Gladys Kontoh; Abu Yaya; John Kwame Bediako; Vitus Apalangya (Applied Food Research, 2023)
Packaging materials are critical in ensuring the safety and quality of foods. Conventional packaging materials from non-renewable sources have revolutionized the food packaging industry, driven largely by convenience, low cost, good moisture barriers, and exhibition of excellent mechanical and handling properties. However, the growing ecological crisis and health burden emanating from heterogenous plastic waste demands sustainable and biodegradable alternatives, which promote circularity and lead to responsible material consumption. Beyond protection and containment, sustainable food packaging materials, unlike their traditional fossil cousins, leave minimal environmental impact and low carbon footprint from birth to dust. There is, therefore, a growing body of research on sustainable food packaging systems from different classes of natural polymers derived mainly from plants and animals. Bio-based packaging materials have been identified as possible renewable sources that can potentially replace conventional packaging materials. They can be extracted from biomass, chemically synthesized, or produced by microorganisms. Besides, they can be processed using wet and dry processes, and other complementary processes. Bio-based materials are generally abundant in nature, and their sources can be broadly categorized into polysaccharides, proteins, and polyhydroxyalkanoates. Though noted as renewable sources, their application has some limitations, such as difficulty in processing and poor performance. However, they can be blended with other materials to overcome these limitations, improving their intrinsic and extrinsic properties, thereby increasing their applicability in the food industry. This review aims to provide an overview of bio-based packaging materials and their consideration for sustainable food packaging. Besides, it discusses the properties critical for their application in the food industry, their limitations, and prospects.